IF 고강도 합금화 용융아연도금강판의 표면품질에 미치는 합금원소의 영향 - 전선호; Sun Ho Jeon; 진광근; Kwang Geun Chin; 신광수; Kwang Soo Shin; 손호상; Ho Sang Sohn; 김대룡; Dai Ryong Kim (대한금속·재료학회지, 46(5), 2008)
The effect of the alloy elements(Si/Mn) ratio on the coating quality including wettabilty with molten zinc, galvannealing kinetics and crater has been investigated in interstitial-free high strength steel(IFHSS) containing Si and Mn. When the Si/Mn ratio was below 0.75, IF-HSS exhibited a good wettability leading to a good galvannealed coating quality after annealing at 800℃ for 40s in15%H2-N2 mixed gas with dew point ?60℃. In contrast, the wettability and galvannealed coating quality were deteriorated in the Si/Mn ratio above 0.75. It is shown that they have relevance to oxides forms by selective oxidation on the steel surface. The oxide particles dispersed on the steel surface with a surface coverage of below 40% resulted in good wettability and galvannealed coating quality. The oxide particle is mainly consisted of Mn2SiO4 with low contact angle in molten zinc. On the other hand, the continuous oxide layer on the steel surface, such as network- and film-type,caused to poor wettability and galvannealed coating quality. The coverage of oxide layer was above 80%, and its chemical species was SiO2 with high contact angle in molten zinc. Consequently, the Si/Mn alloy ratio played an importance role in galvannealed coating quality of IF-HSS.